2000
DOI: 10.1002/(sici)1097-0096(200001)28:1<34::aid-jcu5>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic findings in grade III dengue hemorrhagic fever in adults

Abstract: Purpose Sonography has been used to evaluate children with dengue hemorrhagic fever, but to our knowledge no such studies have been conducted with adults. We present the sonographic findings in 40 adults with severe (grade III) dengue hemorrhagic fever (DHF). Methods Forty patients (30 men and 10 women, aged 16–65 years) given a presumptive diagnosis of grade III dengue hemorrhagic fever during a documented regional epidemic underwent abdominal sonography. Ten also underwent chest radiography. Serologic confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 8 publications
(13 reference statements)
1
28
1
4
Order By: Relevance
“…The diagnosis of DF is often delayed owing to time taken for availability of serology test results [14]. Ultrasonography (USG) is a cheap, rapid and widely available non-invasive imaging method [15,16]. Some authors concluded findings of hepatomegaly, pericholecystic edema, thickened gall bladder, ascites, pleural effusion (right sided/ both) and splenomegaly are early and significant markers of dengue, which can be confirmed by serology later on [17,18].…”
Section: Issn: 2320-5407contrasting
confidence: 81%
See 1 more Smart Citation
“…The diagnosis of DF is often delayed owing to time taken for availability of serology test results [14]. Ultrasonography (USG) is a cheap, rapid and widely available non-invasive imaging method [15,16]. Some authors concluded findings of hepatomegaly, pericholecystic edema, thickened gall bladder, ascites, pleural effusion (right sided/ both) and splenomegaly are early and significant markers of dengue, which can be confirmed by serology later on [17,18].…”
Section: Issn: 2320-5407contrasting
confidence: 81%
“…In a study by Quiroz-Moreno et al [33] gallbladder thickening was seen in 86% of the patients, Sai et al [14] observed in 56% patients whileThulkar et al in 35.1% [34]. Setiwan et al attempted to investigate whether gall bladder wall thickening measured by ultrasonography can be used to predict the onset of severe dengue fever.…”
Section: Discussion:-mentioning
confidence: 99%
“…9 Abdominal sonographic findings in DF are a thickened gallbladder wall, ascites, splenomegaly and pleural effusion. 10 Contrary to this, some authors have described a typical reticular pattern of gall bladder wall thickness that can be used to diagnose and follow up patients with severe DF but should not be considered as an acalculus cholecystitis. 11 Acalculous cholecystitis should be suspected in patients infected with dengue complaining of abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…The thickening of gallbladder wall is the most frequent (43-59%) ultrasonographic finding in patients with dengue fever [15,16] whereas in the case of dengue haemorrhagic fever it may be found in up to 90% of patients [17][18][19][20]. The condition occurs in 7.6% to 38% of patients [9,21,22].…”
Section: Discussionmentioning
confidence: 99%